The emerging digital future : an overview of broadband and multimedia networks - Morley, John, 1949- (Boyd and Fraser, 1998)
Converging realities. Emerging issues. Networks today. Choosing a carrier. Choosing communication services. Connectivity. Frame relay. ATM and STM (asychronous and synchronous transfer modes)...